Koncepcja wykorzystania komputerowej bazy danych wskaźników środowiskowych INDECAM w wybranym przedsiębiorstwie przemysłowym - Rutkowska, Maria; Pigłowski, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The problem of human impact on the environment becomes very important. In the last years, particularly in the industry enterprise, very common becomes the environmental management system according to the ISO 14001 standard. In this system the measurable environmental objectives and targets should be stated. The useful tool for the checking of these objectives and targets realization could be "INDECAM" environmental indicators computer database. In the article the following stages of creating of this database are presented. Then the project and the verification of database are presented. In the end of the article the potential possibilities of using of this tool are proposed. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 239-244